Could the interaction between LMX1B and PAX2 influence the severity of renal symptoms? - Negrisolo, Susanna; Schaefer, Franz (European journal of human genetics, 2018)
Nail Patella syndrome (NPS) is a rare autosomal dominant disease characterized by varying degrees of patella, nail, and elbows dysplasia and also ocular and renal congenital abnormalities. The renal involvement, ranging from hematuria and proteinuria to end-stage renal disease, is present in 22-60% of NPS cases. Heterozygous variants in LMX1B are known to be responsible of NPS and it has been hypothesized that the variable expressivity is due to the interaction of LMX1B with other developmental genes. We reported a case of co-presence of LMX1B and PAX2 variants in a child with extrarenal manifestation of NPS and end-stage renal disease but congenital bilateral renal hypodysplasia and vesicoureteral reflux. The LMX1B variant was de novo, whereas the PAX2 variant was inherited from the mother that had bilateral renal hypoplasia although in presence of only a mild chronic kidney disease. The molecular interaction between LMX1B and PAX2 has been already reported in vitro and this finding suggest that the worst renal NPS phenotype of our patient could be due to the defective expression of these two genes during nephrogenesis. In conclusion, our finding suggests that PAX2 may act as modifier gene in Nail Patella phenotype.